Proximity Effects of Methyl Group on Ligand Steric Interactions and Colloidal Stability of Palladium Nanoparticles - Tieu, Peter; Nguyen, Vincent; Shon, Young-Seok (Frontiers in Chemistry, 2020)
Metal nanoparticle catalysts functionalized with small, well-defined organic ligands are important because such systems can provide a spatial control in the catalyst-substrate interactions. This article describes the synthesis, stability, and catalytic property evaluations of four different Pd nanoparticles capped with constitutional isomers of pentanethiolate ligands that have either a straight chain or an alkyl chain with one methyl group at different locations (α, β, or γ from the surface-bound sulfur). The structure and composition analyses of Pd nanoparticles confirm that they have similar average core sizes and organic ligand contents. The presence of methyl group at α position is found to lower the capping ability of short ligands and thus make Pd nanoparticles to lose their colloidal stability during the catalytic reactions. The overall activity and selectivity for hydrogenation and isomerization of pentene and allylbenzene derivatives are investigated for each combination of ligand and substrate. Catalysis results indicate that steric interactions between the ligands on the metal catalyst surface and the alkene substrates are a factor in controlling the activity of Pd nanoparticles. In particular, Pd nanoparticles capped with pentanethiolate isomer having a methyl group at α position exhibit poor and inconsistent catalytic activity due to its low colloidal stability. The presence of a methyl group at β position mildly interferes the adsorption of alkene group on the nanoparticle surface resulting in lower conversion yields. Interestingly, a methyl group at γ position only has a minimal effect on the catalytic property of Pd nanoparticles exhibiting similar catalysis results with Pd nanoparticles capped with straight chain pentanethiolate ligands. This indicates the proximity of steric group at the reactive site controls the nanoparticle activity for surface oriented reactions, such as hydrogenation and isomerization of alkenes in addition to their colloidal stability.